Survey on the presence of floating microplastics, trace metals and metalloids in seawater from Southern Italy to the United States of America - Elisabetta Morici; Gaetano Cammilleri; Sergio Scirè; Francesco Paolo Bonomo; Luigi Tranchina; Francesca Terracina; Paola Galluzzo; Vincenzo Ferrantelli; Vincenzo Paolo Monteverde; Francesco Giuseppe Galluzzo; Sergio Davì; Mariano Licciardi; et al. (Ecotoxicology and Environmental Safety)
The presence of microplastics (MPs), trace metals (TM) and metalloids (Ms) in surface seawater is a severe emerging issue of global concern. Information about the distribution of these pollutants is often lacking, and large-scale studies come with uncertainties because of difficult comparisons of results obtained using different methods to collect and process data. This study presents a comprehensive investigation of microplastics (MPs), trace metals (TM) and metalloids (Ms) in surface seawater during two transatlantic sampling campaigns, covering approximately 17,000 nautical miles. The results reveal the presence of MPs in all the samples analyzed and a broad variation in microplastic concentration (230–3320 MPs/L), with filaments or fibers being the most abundant shape. Coastal waters generally exhibit higher MPs, TM and Ms concentrations than open sea waters. The results showed high concentrations of MPs, particularly in the waters near the Faroe Islands, in the Sea of Magdalena department and in the Strait of Gibraltar. The order of the overall metals and metalloids concentrations was: As>Cr>Pb>Cd. High concentrations of Pb and Cr were recorded in the Mediterranean waters whereas high Arsenic (As) were found in the Southern coasts of United States, with values that exceeded the limits considered hazardous for aquatic life (81.55–101.12 µg/L). No significant correlations were found between microplastics, and the heavy metals examined. Here, we emphasize the need for sustainable environmental management actions and policies in a global context to monitoring the growing problem of pollutants in our oceans.